Математична модель оптимального керування рухом електрорухомого складу на підставі вирішення рівнянь Гамільтона-Якобі-Беллмана - Петренко, Олександр Миколайович; Любарський, Борис Григорович (Українська державна академія залізничного транспорту, 2016)
У роботі розроблена математична модель системи управління електрорухомим складом, заснована на рішенні рівняння Гамільтона-Якобі-Беллмана з використанням методу динамічного програмування і зворотного рішення задачі відносно координати часу – "зворотний підхід Беллмана". При цьому передбачається, що кінцева точка руху електрорухомого складу відома – кінцева координата переміщення і заданий час руху, а кінцева швидкість в цій точці дорівнює нулю – що відповідає прибуттю потягу.

Optimal control is a powerful tool, which allows you to solve complex management tasks, including motion control of electric rolling stock on railways. The optimization problem is a common concern of management theory. It consideres the current factor as an abstract object, which seeks to maximize the expected benefits (or minimize losses) at some future period of time. A mathematical model of electric rolling stock control systems, based on the solution of Hamilton-Jacobi-Bellman equation using the method of dynamic programming and reverse solution of the problem relating to the time coordinate has been developed in this paper. To reduce the volume of calculations it has been proposed to determine the optimal expert system in the reverse direction relating to the movement time of electric rolling stock - "reverse Bellman approach." It is assumed that the end point of electric rolling stock movement is known - the ultimate coordinate of movement and given time of movement, and the final velocity at this point is zero - which corresponds to the arrival of the train to the destination.
Mathematical model of optimal motion control of electric rolling stock based on the solution of Hamilton-Jacobi-Bellman
Keywords: точка руху; динамічне програмування; потяг; дискретний час; електрорухомий склад; movement control; optimal traffic management; dynamic programming